Tartrazine Increases Oxidative Stress and Modulates the Expression of Apoptotic-Regulatory Genes in Drosophila melanogaster - Wusu, Adedoja D.; Oyeniran, Modupe O.; Igbalaye, Jimoh O.; Rotimi, Solomon O.; Afolabi, Olusegun K. (Polish Journal of Natural Sciences, 2023)
In this study, the effect of exposure to a food colorant tartrazine was investigated on biomarkers of oxidative stress and apoptosis in Drosophila melanogaster. D. melanogaster eggs were grown on cornmeal medium containing tartrazine at different concentrations (0, 250, 500, 1000, 2000 mg/kg). Third instar larvae of D. melanogaster were harvested. Oxidative stress markers were assayed spectrophotometrically while the level of expression of some apoptosis-regulatory genes were quantified using reverse polymerase chain reaction technique. Tartrazine significantly (p < 0.05) increased the levels of hydroperoxides and malondialdehyde in a dose-dependent manner. Interestingly, glutathione level increased among the groups, while the activities of glutathione transferase were reduced across the treatment groups. Tartrazine exposure resulted in misexpression of apoptosis and stress genes with a significant reduction in ANCE, HSP 27 genes. This study suggests that tartrazine induced oxidative stress and could induce apoptosis in D. melanogaster larvae, thus a risk factor in developmental toxicity.